Influence of Work Experience and Education towards Business Performance among Entrepreneurs - Othman, Nor Hafiza; Md Pazil, Afifah Hanim; Mat Zaib, Siti Zamanira; Jin, Chuk Wei; Attaullah, Siti Aishah; Mahadi, Nur Fatin Diyana (International Business Education Journal, 2016)
Prior experience of entrepreneur can decrease the amount of uncertainty and it might give motivation or encourage them to bear uncertainty. Through education, it can help entrepreneurs to have a critical thinking and expose them to the new business potential or benefits in globalization era. So, it is important to understand prior work experience and education of entrepreneurs because it will affects the business performances. The aim of this study was to determine the influence of work experience and education towards business performance among entrepreneurs in Kelantan. Simple random sampling procedures, a total of 379 entrepreneurs were selected and participated in this survey. The data from structured questionnaire was analysed by regression analysis (stepwise) in this study. The finding shows that the work experience of entrepreneurs influenced more than entrepreneurs education towards business performances. Therefore, exposure on the real business experience in university and college should be included in entrepreneurship education courses curriculum to have more successful entrepreneurs.